«I called on the audience to strive for possible simple cessation of the war»: the arrest of Omsk social-democrat K. A. Popov in January 1916 - M. M. Stelmak (Омский научный вестник: Серия "Общество. История. Современность")
This publication reconstructs the causes, circumstances and consequences of the arrest of the Omsk Social Democrat, lawyer K. A. Popov by the gendarmerie in Omsk in January 1916, despite a considerable number of materials on the biography of K. A. Popov, the history of the revolutionary movement in Omsk, a separate study , entirely dedicated to this event, has not yet been published. The basis for the publication is the documents of the paperwork of the gendarmerie identified in the funds of the historical archive of the Omsk region. According to the results of a study built on a combination of an anthropological approach and the biographical method, the author emphasizes the special importance of the documentary heritage of domestic special services that provide significant assistance in the study of sociopolitical history.